If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 3x = 3 + 5x Solving 5 + 3x = 3 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 5 + 3x + -5x = 3 + 5x + -5x Combine like terms: 3x + -5x = -2x 5 + -2x = 3 + 5x + -5x Combine like terms: 5x + -5x = 0 5 + -2x = 3 + 0 5 + -2x = 3 Add '-5' to each side of the equation. 5 + -5 + -2x = 3 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = 3 + -5 -2x = 3 + -5 Combine like terms: 3 + -5 = -2 -2x = -2 Divide each side by '-2'. x = 1 Simplifying x = 1
| 8w-5=35-12w | | x-2x=200 | | (9a^2-4-5a)-(12a-6a^2+3)= | | x-2x=300 | | (3+5i)-(4-6i)= | | -17=6x-(1+2x) | | 3k^5+4k^2-6k^5-5k^2= | | X-2=5-x | | 3xy-7x(5y-4m)= | | 4b+7a=10 | | -4x^4+x^2-10+12x^4-7x^2= | | 16z-11+2z+1=-1 | | 4-5v-12v-6v^2-4-2v^3= | | 7x^2+22x-2=0 | | y^2+2y+5-3y^2-5y= | | 7x^2+23x-8=0 | | 2y-5y+8y=30 | | 5x^2+18x-4=0 | | 15x-5=7x+7 | | 7x^2+12x-7=0 | | X-2.5=-7.1 | | 104-6x=30x+24 | | 8x+5y-3x+y=0 | | 8x-26=4x+54 | | F(-4)=-x^2-2x | | 3x-4+3x=14 | | 5w+(-16)=-76 | | (6x+9)-4x+1=0 | | X=6-7 | | x^2-9x-162=0 | | X=5+9 | | |2x+5|+4=1 |